Aurora-B kinase pathway controls the lateral to end-on conversion of kinetochore-microtubule attachments in human cells - Roshan L. Shrestha (Nature Portfolio, 2017)
Human chromosomes are captured along microtubule walls and then tethered to microtubule-ends through a multi-step end-on conversion process. Here the authors show that Aurora-B regulates end-on conversion in human cells and establish a late role for Astrin-SKAP complex in the end-on conversion process.